Telomeric and Sub-Telomeric Structure and Implications in Fungal Opportunistic Pathogens - Diotti, Raffaella (Microorganisms, 2021)
Telomeres are long non-coding regions found at the ends of eukaryotic linear chromosomes. Although they have traditionally been associated with the protection of linear DNA ends to avoid gene losses during each round of DNA replication, recent studies have demonstrated that the role of these sequences and their adjacent regions go beyond just protecting chromosomal ends. Regions nearby to telomeric sequences have now been identified as having increased variability in the form of duplications and rearrangements that result in new functional abilities and biodiversity. Furthermore, unique fungal telomeric and chromatin structures have now extended clinical capabilities and understanding of pathogenicity levels. In this review, telomere structure, as well as functional implications, will be examined in opportunistic fungal pathogens, including Aspergillus fumigatus, Candida albicans, Candida glabrata, and Pneumocystis jirovecii.